A critical examination of online banking scam in Nigeria: Kano Metropolis in view - Aliyu, Alhaji Abubakar (2012)
Electronic banking frauds are becoming a global phenomenon in nature, while its consequences are becoming a great concern for the banks worldwide. This paper tries to investigate the magnitude of online banking frauds in Nigerian commercial banks and proffer lasting solutions that will mitigate this contending and boiling issue in the Nigerian banking industry. The paper employs both primary and secondary data in order to investigate the online banking frauds in Nigerian banks. The chi-square statistical technique was used to analyze the data and test the hypothesis raised. The paper concludes that both bank customers and bankers have a joint role to play in stopping the perpetrators of online banking frauds in the banks. The research reveals that phishing attacks appear to be the dominant dimension of online banking frauds in Nigeria followed by fake web site substitution and pharming. While, vishing fraud is not a common phenomenon in Nigeria, it ranked lowest in the ranking of the dimensions.